A non‐chromatographic method for the removal of endotoxins from bacteriophages. Issue 8 (5th May 2015) - Branston, Steven D.; Wright, Jason; Keshavarz‐Moore, Eli
ABSTRACT The Ff filamentous bacteriophages show potential as a new class of therapeutics, displaying utility in materials science as well as pharmaceutical applications. These phages are produced by the infection of E. coli, a Gram‐negative bacterium which unavoidably sheds endotoxins into the extracellular space during growth. Since endotoxin molecules are highly immunoreactive, separation from the phage product is of critical importance, particularly those developed for human therapeutic use. The properties of M13, one of the Ff group, present a purification challenge chiefly because the standard scalable method for endotoxin removal from proteins—anion exchange chromatography—is not applicable due to pI similarity between the particles. This article examines the potential of polyethylene glycol (PEG)–NaCl precipitation as a scalable method for the separation of endotoxins from phage M13. Precipitation of M13 by 2% (w/v) PEG 6 000, 500 mM NaCl reduced endotoxin contamination of the phage product by 88%, but additional precipitation rounds did not maintain this proportional decrease. Dynamic light scattering was subsequently used to determine the effectiveness of a detergent to disassociate endotoxin molecules from M13. As a result, PEG–NaCl precipitation was supplemented with up to 2% (v/v) Triton X‐100 to improve separation. A 5.7 log10 reduction in endotoxin concentration was achieved over three rounds of precipitation whilst retaining over 97% of the phage. This method compares favorably with the well‐known ATPS (Triton X‐114) technique for endotoxin removal from protein solutions. Biotechnol. Bioeng. 2015;112: 1714–1719. © 2015 Wiley Periodicals, Inc.